2016
DOI: 10.1038/pr.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

Milk growth factors and expression of small intestinal growth factor receptors during the perinatal period in mice

Abstract: Gene expression of small intestinal GF receptors is likely a process of neonatal intestinal maturation that is affected concurrently by milk GFs and additional endogenous factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Human milk contains different isoforms of TGF-β, which are more abundant in colostrum than in mature milk [71,72], and TGF-β2 is the most abundant (95%) [72,73]. In mice, it was previously demonstrated that TGF-β1 concentration in milk is higher than TGF-β2 [68]. In our study, TGF-β1 was not detected, corresponding with Penttila et al who did not find it in rat milk either [74].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Human milk contains different isoforms of TGF-β, which are more abundant in colostrum than in mature milk [71,72], and TGF-β2 is the most abundant (95%) [72,73]. In mice, it was previously demonstrated that TGF-β1 concentration in milk is higher than TGF-β2 [68]. In our study, TGF-β1 was not detected, corresponding with Penttila et al who did not find it in rat milk either [74].…”
Section: Discussionsupporting
confidence: 78%
“…Little is known about its concentration in rat milk, and its levels in humans were determined in studies from more than 30 years ago. In rodents, the concentration of EGF in milk is about 120-450 ng/mL in mice [67,68] and 10-31 ng/mL in rat [69]. However, it should be taken into account that in this study, milk was obtained from Sprague-Dawley rats.…”
Section: Discussionmentioning
confidence: 97%
“…This concept, that exogenous TGFβ supplements endogenous gut TGFβ, is similar to one proposed by Penttila et al (1998) who found that maternal milk was rich in this growth factor. A recent mouse study by Zhang et al (2016) used QPCR to measure levels of a variety of growth factor receptors in small intestine between E13 and postnatal day 60. They found that transcripts encoding TGFβ-RI were highest at E13, and fell later in gestation, then rose to a smaller peak at 2 weeks after birth.…”
Section: Sources Of Tgfβ In Vivomentioning
confidence: 99%
“…Transcripts encoding TGFβ-RII rose between E13 and 2 weeks after birth, and then decreased. The study reported that milk contained an average of 900 ng/ml of TGFβ1 at birth, with levels of TGFβ2 approximately an order of magnitude less (Zhang et al, 2016). In the first few postnatal weeks, the authors contended that TGFβ proteins in milk may affect epithelial terminal differentiation, and play an anti-inflammatory effect, in the small intestine.…”
Section: Sources Of Tgfβ In Vivomentioning
confidence: 99%
“…However, maternal care may not be the only postnatal mechanism influencing adult offspring behavior. For example, breastmilk provides not only nutrients but also a plethora of biologically active compounds, including cytokines and growth factors ( Dvorak, 2010 ; Garofalo, 2010 ; Zhang et al., 2016 ) that, via gut-brain communication ( Powell et al., 2017 ; Foster et al., 2017 ; Fung et al., 2017 ), may influence brain development and behavior ( Walfisch et al., 2013 ; Lucas et al., 1992 , 1994 ). Indeed, some studies suggested the beneficial effect of breastfeeding over formula on the cognitive and emotional development of full and preterm infants ( Lucas et al., 1992 ; Der et al., 2006 ; Kramer et al., 2008 ; Yang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%